Generalized digital lithological map of northern Mexico and southwestern United States of America - Arlin Brighith Fonseca Martínez; Kevin Mexia-Durán; Gustavo Adolfo Ramírez-Salamanca; Alexander Iriondo (Terra Digitalis)
The compilation and generalization of the lithological units that crop out in northern Mexico and southwestern United States of America are important to understand the geology and evolution of this part of the North American continent. For this reason, we publish the first interactive digital lithological map with eleven surficial lithological units present in northern Mexico and southwestern United States of America, in which equivalent formations, sequences and igneous units of both countries were merged and generalized. This map shows the distribution of the main types of rocks that evolved in similar geological processes through time, therefore, researchers can use this new compiled map in the analysis and location of samples and geological evolution, or even during studies related to exploration of natural resources. The area covered by the map is comprised between Longitude of 123°10’W and 94°42’W and Latitude of 23°03’N and 36°57’N (Datum WGS-84).